2022
DOI: 10.3389/fphar.2022.886981
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Supramolecular Mesoporous Silica Nanoparticles as the Next-Generation Drug Delivery System

Abstract: Supramolecular mesoporous silica nanoparticles (MSNs) offer distinct properties as opposed to micron-sized silica particles in terms of their crystal structure, morphology–porosity, toxicity, biological effects, and others. MSN biocompatibility has touched the pharmaceutical realm to exploit its robust synthesis pathway for delivery of various therapeutic molecules including macromolecules and small-molecule drugs. This article provides a brief review of MSN history followed by special emphasis on the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…The biocompatibility of MSNs, as an ideal drug delivery nanocarrier, has been extensively studied and reported, recently. [48][49][50] MSNs-CDs, in contrast to MSNs, represent the highest cytotoxicity on all the studied cell lines. The results of statistical analysis showed that the anticancer effect of MSNs-CDs, on both cancer cell lines, is signicantly higher than the free CDs.…”
Section: In Vitro Studiesmentioning
confidence: 88%
“…The biocompatibility of MSNs, as an ideal drug delivery nanocarrier, has been extensively studied and reported, recently. [48][49][50] MSNs-CDs, in contrast to MSNs, represent the highest cytotoxicity on all the studied cell lines. The results of statistical analysis showed that the anticancer effect of MSNs-CDs, on both cancer cell lines, is signicantly higher than the free CDs.…”
Section: In Vitro Studiesmentioning
confidence: 88%
“…This is because by altering the physical form of API, one can improve, among others, the dissolution properties of drug compounds, ultimately increasing their bioavailability and therapeutic efficacy. It is crucial, especially because approximately 40% of marketed drugs reveal poor aqueous solubility. Furthermore, it is anticipated that up to 90% of new chemical entities will encounter this issue and thus might be rejected from the research and development pipeline. , The recalled statistics highlight the significance of developing effective strategies to improve the solubility of drugs and thus enhance their therapeutic efficacy and patient outcomes. In the literature, many reports prove that API’s aqueous solubility, bioavailability, and dissolution rate can be improved even a dozen times when it is converted to an amorphous or metastable polymorphic form. …”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many reports prove that API’s aqueous solubility, bioavailability, and dissolution rate can be improved even a dozen times when it is converted to an amorphous or metastable polymorphic form. 10 15 …”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous silica nanoparticles (MSNs) have garnered attention as potential drug delivery systems due to their unique structural and physicochemical properties, including high surface area, large pore volume, and tunable pore size. These features enable efficient drug loading, controlled release, and targeted delivery to specific cells or tissues. In this study, we propose novel pH-triggered DCLs combined with large-pore MSNs (LPMSNs), referred to as LPMSN-laden DCLs. These drug nanocarriers do not require prior drug loading and are compatible with the commercial manufacturing process for CLs.…”
Section: Introductionmentioning
confidence: 99%